Penerapan Pembelajaran Kontekstual melalui Kegiatan Menanam Sayuran pada Anak Usia Dini di RA. Aladdin Lombok Barat - Afifah Farida; Dwi Noorma Putri; suprayanti Martia Dewi; Reni Apriani (Jurnal Gema Ngabdi, 2026)
Early childhood education plays a crucial role in shaping children’s cognitive development, social skills, and character formation. However, learning practices in many early childhood education institutions are still dominated by classroom-based activities with limited direct experience. This community service program aimed to implement contextual learning through vegetable planting activities for early childhood learners at RA Aladdin, West Lombok, to enhance learning experiences, environmental awareness, and social skills. The partners involved were teachers and students of RA Aladdin. The program employed an educative participatory approach based on Contextual Teaching and Learning (CTL), implemented through three stages: preparation, implementation, and evaluation. During the implementation stage, children were directly involved in planting and caring for vegetables in the school yard under the guidance of teachers. Evaluation was conducted through participatory observation to assess children’s engagement and enthusiasm, as well as reflective discussions with teachers to evaluate program effectiveness and sustainability. The results showed that contextual learning through vegetable planting increased children’s active participation, fostered responsibility and cooperation, and helped them understand basic plant concepts through direct experience. This activity also strengthened teachers’ roles as learning facilitators. Overall, the program highlights the importance of utilizing the school environment as a contextual learning resource to support meaningful and sustainable learning in early childhood education.